Juglanin Inhibits Osteoclastogenesis in Ovariectomized Mice via the Suppression of NF-κB Signaling Pathways - Zhang, Fangxue; Huang, Xiaowei; Qi, Yuhan; Qian, Zhi; Ni, Shuo; Zhong, Zeyuan; Zhang, Xu; Li, Dejian; Yu, Baoqing (Frontiers in Pharmacology, 2021)
Bone metabolism is a physiological process that involves both osteoblasts and osteoclasts. Pathological changes of osteoclasts are commonly seen in osteoporosis diseases. Juglanin is a natural compound, reported to have an inhibitory effect on inflammation, oxidative stress and cancer progression. The purpose of this study is to explore the role that Juglanin plays on the osteoclast functions and underlying signaling pathways. In vitro study demonstrated that Juglanin had negative influence on osteoclastic differentiation by suppressing the transcription activity of osteoclastogenesis-related genes and proteins. To determine the underlying mechanism, Western blot was employed to show that Juglanin could significantly have negative effect on the phosphorylation of P50, P65, I-κB， ultimately suppressing the expression and transcriptional activity of nuclear factor of activated T cells(NFATc1). In vivo, Juglanin treatment attenuate bone reducing in mice with removed ovary through suppressing osteoclast functioning. Taken together, our study demonstrated that In the molecular mechanism, JUG inhibited the expression of RANKL induced NF - κ B signaling pathway, thus may play an vital part in preventing postmenopausal osteoporosis.